O niektórych możliwościach zastosowania metod matematycznych w dydaktyce literatury = On certain possibilities of mathematical methods applications within the literature didactics - Trochanowski, Włodzimierz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper is devoted to ccrtain applications of mathematical methods within the literature didactics. It is concerned with four main applications which have heen discussed: a) the application of graphemes and matrix to the examination of the structure of the teaching content, the distribution of the teaching material and the unit - structure in the discussion of the literary piece of work.
Keywords: dydaktyka literatury; metody matematyczne